Ijtihad sebagai Sarana Merajut Nilai Kemaslahatan dan Keadilan Umat - Moh. Roqib (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2007)
Islam is prominent and actual in every occation, however problrms are always rising. To handle those problems, ijtihad or a process to obtain operational Islamic law is considered by some Moslem scholars as one solutions. Ijtihad which is relative and tentantive is used for gaining the shari’a’s aim (maqasid al-shari’a), society peaceful (maslahah ‘ammah).